A kind of old rain sewage pipeline non-excavation repair two-component quick-setting epoxy lining repair mortar
Patent Information
- Application Number
- CN202611239958.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的在于提供一种专门针对老旧雨污管道非开挖带水修复场景的双组份快凝环氧内衬修复砂浆,以解决现有环氧砂浆在潮湿基面附着力差、固化慢、喷涂厚度不均、耐污能力弱等问题
本发明突破常规富树脂环氧砂浆的配比思维,将A:B质量比确定为1:2.5~3.0,并相应提高B组分中聚酰胺固化剂的含量,使固化剂实际供给量与环氧树脂和活性稀释剂的总量相匹配。该特定配比与改性聚酰胺固化体系的协同作用,使砂浆在管道内壁潮湿乃至有明显积水条件下,无需预先烘干即可直接喷涂并快速固化,修复层与基面附着牢固,从根本上解决了现有环氧砂浆遇水乳化、发白、粘接失效的顽疾。A:B=1:2.5~3.0的配比使砂浆呈现富骨料、足固化剂的特征,大量石英细砂、硅微粉和耐腐重钙粉构建了级配良好的骨料骨架。该骨架在离心喷涂时赋予砂浆理想的流变特性,既能在离心力作用下顺利铺展至管壁各部位,又能在静止后迅速建立结构强度,有效杜绝了常规砂浆常见的管道底部堆积、顶部挂壁过薄问题,一次喷涂即可形成厚度高度均匀的内衬层。得益于高B组分比例带来的充足固化剂供给,砂浆的固化反应速率显著提高。B组分中大量引入的偶联剂处理耐腐重钙粉和硅微粉,在高配比下于内衬层中形成致密的复合防腐屏障。该屏障能有效抵抗生活污水、工业废水中酸碱介质和硫化物的长期渗透与侵蚀。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of trenchless repair materials for underground pipelines, specifically to a two-component fast-setting epoxy lining repair mortar for trenchless centrifugal spraying repair of old rainwater and sewage pipelines in humid environments. Background Technology
[0002] Over long-term service, underground stormwater and sewage pipes in old urban areas commonly suffer from severe damage such as internal wall corrosion, cracks leading to water seepage, and joint leaks. Traditional open-cut pipe replacement methods are costly and severely disrupt traffic, making large-scale implementation difficult in old urban areas. Therefore, trenchless spray lining repair technology has become the mainstream choice. However, existing lining repair materials still have many shortcomings in terms of construction performance and durability, especially in the scenario of rapid repair on wet or damp pipe surfaces, where an ideal solution remains elusive.
[0003] Specifically, existing pipe lining repair materials mainly face the following challenges: (1) Ordinary single-component epoxy mortar cures slowly. Under conditions of water accumulation or wet inner wall in the pipe, the coating adhesion decreases sharply, and the repair layer is prone to peeling and falling off. (2) Conventional lining mortar has poor resistance to corrosive media such as acids, alkalis and sulfides in domestic sewage and industrial wastewater. The repair layer will powder and peel off within 3 to 5 years, resulting in a short service life. (3) The viscosity of existing materials is not easy to adjust during spraying construction, and the bottom of the pipe is prone to accumulation, while the thickness of the wall at the top is insufficient, making it difficult to form a uniform inner lining; (4) The curing time is greatly extended when construction is carried out at low temperature or during the rainy season, and the repair cycle of a single section of pipeline is long, which seriously affects the timely restoration of urban drainage and easily leads to waterlogging and sewage overflow.
[0004] To improve the workability of epoxy mortar, existing technologies have proposed improvements from the perspective of thixotropy. Chinese patent CN120682596A discloses a high-thixotropic epoxy mortar. Its component A contains epoxy resin, filler, reactive diluent, thixotropic agent, and toughening agent; component B contains thiourea-modified aliphatic primary amine curing agent, wear-resistant filler, inert diluent n-butanol, and accelerator DMP-30. The mass ratio of component A to component B is 10:3 to 10:4, or approximately 1:0.3 to 1:0.4. This formulation imparts thixotropic properties to the mortar through a large amount of thixotropic agent, making it less prone to sagging during application and pouring, and suitable for building repairs, floor reinforcement, etc.
[0005] However, the aforementioned high-thixotropic epoxy mortar is completely unsuitable for trenchless repair of old stormwater and sewage pipes in wet conditions. The reasons are as follows: First, the high proportion of epoxy resin in its A and B components results in a dense and hard resin-based composite material after curing, but with extremely poor tolerance to damp surfaces. The curing agent, thiourea-modified aliphatic primary amine, emulsifies and whitens upon contact with water, leading to bonding failure. Second, the formulation uses the inert organic solvent n-butanol, which releases irritating and toxic gases during construction in confined underground spaces, posing a serious safety hazard. Third, the rheological properties in the high-thixotropic state are mainly suitable for troweling and scraping processes. During centrifugal spraying of pipes, the excessively high static viscosity hinders the uniform spreading of the material under centrifugal force, resulting in uneven lining thickness. Fourth, the low proportion of aggregates and fillers results in insufficient wear resistance and sewage corrosion resistance of the lining, making it difficult to withstand long-term sewage erosion and corrosion. More importantly, the existing technology has never recognized the decisive impact of the A and B group ratio on the repair of water-bearing centrifugal spraying of pipelines, nor has it provided any insights into adjusting the ratio to solve the aforementioned problems.
[0006] Therefore, there is an urgent need to develop an epoxy lining repair mortar with fundamental innovations in the composition and ratio of components A and B, in order to meet the requirements of rapid spraying, uniform molding, safety and durability on the wet and water-bearing base surface of old rainwater and sewage pipes. Summary of the Invention
[0007] The purpose of this invention is to provide a two-component fast-setting epoxy lining repair mortar specifically designed for trenchless repair of old stormwater and sewage pipes in wet conditions, in order to solve the problems of poor adhesion, slow curing, uneven coating thickness, and weak stain resistance of existing epoxy mortars on damp substrates.
[0008] Specifically, to address the aforementioned issues, a two-component, fast-setting epoxy lining repair mortar for trenchless repair of old stormwater and sewage pipes is provided. This mortar consists of component A and component B, which are pre-mixed separately. During construction, the mass ratio of component A to component B is 1:2.5–3.0. (By weight, ...) The A component consists of the following components: 60-70 parts of bisphenol A epoxy resin, 10-15 parts of reactive diluent, 1-3 parts of defoamer, and 1-2 parts of wetting and penetrating agent. The B component consists of the following components: 50-65 parts of fine quartz sand, 15-25 parts of silica powder, 25-40 parts of polyamide curing agent, 10-15 parts of corrosion-resistant heavy calcium carbonate powder with surface treated by silane coupling agent, and 1-3 parts of coagulation accelerator. Furthermore, neither component A nor component B contains inert organic solvents.
[0009] The core concept of this invention lies in abandoning the conventional approach of using epoxy resin-rich formulations in the field. By significantly increasing the amount of component B to 2.5 to 3.0 times that of component A, and correspondingly increasing the absolute content of polyamide curing agent in component B, the system is transformed into a mortar rich in aggregate and with a sufficient supply of curing agent. The synergistic effect brought about by this ratio is as follows: First, since component B contains sufficient polyamide curing agent and fine aggregate, after mixing A:B=1:2.5~3.0, the actual supply of curing agent is within a reasonable range relative to the total amount of epoxy resin and reactive diluent, which can react quickly and fully with epoxy groups, and can achieve high-speed curing even under low temperature or humid conditions, and the surface drying time can be shortened. Secondly, a large amount of fine quartz sand, silica powder, and corrosion-resistant heavy calcium carbonate powder constitute a well-graded aggregate skeleton, which can give the mortar appropriate thixotropic and plastic viscosity during centrifugal spraying. It can spread smoothly to the pipe wall under centrifugal force and quickly build up structural strength after the rotation stops, fundamentally eliminating the problems of accumulation at the bottom of the pipe and excessively thin wall at the top, forming a uniform and dense inner lining layer. Third, the high filler content significantly improves the impermeability and wear resistance of the inner lining. In synergy with the corrosion-resistant heavy calcium carbonate powder treated with coupling agent, it can maintain structural integrity under long-term sewage immersion and greatly extend service life. Fourth, during wet construction, sufficient polyamide curing agent can react rapidly with epoxy resin; the wetting and penetrating agent reduces the interfacial tension between the mortar system and the damp substrate, promoting the spreading and penetration of the mortar on the water film on the substrate surface, and assisting in the dissipation of the water film on the substrate surface, allowing the epoxy-amine curing reaction to proceed effectively at the damp interface. In this process, the moisture on the substrate surface does not participate in the cross-linking reaction between the epoxy resin and the polyamide curing agent, but is physically dissipated or isolated, thus avoiding interference with the curing reaction and achieving strong adhesion to the wet substrate.
[0010] Experiments have shown that when the A:B mass ratio is below 1:2.5, component B is insufficient, the curing speed decreases significantly, the lining surface becomes sticky, strength development is slow, and anti-sagging properties deteriorate. When the A:B ratio is above 1:3.0, the mixture becomes too dry, making it difficult to pump and centrifuge, reducing the density of the lining and causing localized cracking. Therefore, a ratio range of 1:2.5 to 3.0 is crucial for achieving optimal balance in all performance aspects.
[0011] Furthermore, the mass ratio of component A to component B is 1:2.8. This ratio achieves an optimal combination of curing speed, adhesion, lining uniformity, and ease of application.
[0012] Furthermore, in component A, there are 65 parts of bisphenol A epoxy resin, 12 parts of reactive diluent, 2 parts of defoamer, and 1.5 parts of wetting and penetrating agent; in component B, there are 55 parts of quartz fine sand, 20 parts of silica powder, 35 parts of polyamide curing agent, 12 parts of corrosion-resistant heavy calcium carbonate powder treated with silane coupling agent, and 2 parts of coagulation regulator.
[0013] Furthermore, the reactive diluent is selected from butyl glycidyl ether, C 12 ~C 14 One or more alkyl glycidyl ethers are included; the defoamer is an organosilicone defoamer; and the wetting and penetrating agent is a polyether-modified polysiloxane. These additives not only reduce the viscosity of the system and eliminate bubbles, but also significantly enhance the mortar's ability to wet and spread on damp substrates. Furthermore, all of them participate in the curing reaction, ensuring that the formulation does not contain inert organic solvents.
[0014] Furthermore, the polyamide curing agent is an adduct of dimer acid-triethylenetetramine condensate and bisphenol A epoxy resin, or a dimer acid type polyamide. The polyamine is selected from at least one of diethylenetriamine, triethylenetetramine, and m-phenylenediamine. The amine value of the polyamide curing agent is 180–220 mgKOH / g. The silane coupling agent used in the corrosion-resistant heavy calcium carbonate powder with surface treatment is KH-550 or KH-560. The coupling agent treatment enhances the interfacial bonding between the filler and the epoxy matrix, and also imparts excellent acid and alkali resistance and sulfide corrosion resistance to the lining layer.
[0015] Furthermore, the coagulating regulator is 2,4,6-tris(dimethylaminomethyl)phenol, and its dosage is adjusted according to the ambient temperature during construction: when the temperature is below 15℃, the dosage is 2.5 to 3 parts; when the temperature is between 15℃ and 25℃, the dosage is 1.5 to 2.5 parts; and when the temperature is above 25℃, the dosage is 1 to 1.5 parts.
[0016] This invention provides a trenchless method for repairing old stormwater and sewage pipes, using the aforementioned two-component fast-setting epoxy lining repair mortar, comprising the following steps: Weigh the pre-prepared components A and B at a mass ratio of 1:2.5 to 3.0, mix them evenly, and then spray the mortar evenly onto the inner wall of the pipe under the action of centrifugal force through a centrifugal spraying device to form an inner lining repair layer. During spraying, the inner wall of the pipe is wet or watery and is not pre-dried.
[0017] Furthermore, during centrifugal spraying, the centrifugal sprayer rotates at a speed of 300–800 rpm, moves at a speed of 0.5–2 m / min, and achieves a single spray thickness of 1–3 mm. The designed repair thickness is achieved through multiple sprays.
[0018] The beneficial effects of this invention are: This invention breaks through the conventional thinking on the proportioning of resin-rich epoxy mortar, determining the A:B mass ratio to be 1:2.5-3.0, and correspondingly increasing the content of polyamide curing agent in component B, so that the actual supply of curing agent matches the total amount of epoxy resin and reactive diluent. The synergistic effect of this specific ratio and the modified polyamide curing system allows the mortar to be directly sprayed and rapidly cured even when the inner wall of the pipe is damp or has significant water accumulation, without the need for pre-drying. The repair layer adheres firmly to the substrate, fundamentally solving the persistent problems of emulsification, whitening, and adhesion failure of existing epoxy mortars upon contact with water. The A:B ratio of 1:2.5-3.0 gives the mortar the characteristics of being rich in aggregate and having sufficient curing agent. A large amount of fine quartz sand, silica powder, and corrosion-resistant heavy calcium carbonate powder construct a well-graded aggregate skeleton. This framework imparts ideal rheological properties to the mortar during centrifugal spraying, allowing it to spread smoothly to all parts of the pipe wall under centrifugal force and rapidly build up structural strength after settling. This effectively eliminates the common problems of conventional mortars, such as pipe bottom accumulation and excessively thin top wall adhesion, allowing for a uniformly thick inner lining layer in a single spray application. Thanks to the ample supply of curing agent resulting from the high proportion of component B, the mortar's curing reaction rate is significantly improved. The coupling agent introduced in large quantities in component B treats the corrosion-resistant heavy calcium carbonate powder and silica fume, forming a dense composite anti-corrosion barrier in the inner lining layer at a high ratio. This barrier effectively resists the long-term penetration and erosion of acidic and alkaline media and sulfides from domestic sewage and industrial wastewater. Detailed Implementation
[0019] The present invention will be further illustrated below with reference to examples and comparative examples, but the present invention is not limited thereto.
[0020] Example 1 Component A: By weight, 65 parts of bisphenol A epoxy resin (E-51), 12 parts of butyl glycidyl ether, 2 parts of silicone defoamer, and 1.5 parts of polyether-modified siloxane wetting and penetrating agent.
[0021] Component B: by weight, 55 parts of 80-120 mesh quartz sand, 20 parts of 800 mesh silica powder, 35 parts of the adduct of dimer acid-triethylenetetramine condensate and E-51 epoxy resin, amine value 200 mg KOH / g, 12 parts of corrosion-resistant heavy calcium carbonate powder treated with KH-550, and 2 parts of DMP-30 accelerator.
[0022] During construction, the mass ratio of A to B is 1:2.8.
[0023] Construction environment: Temperature 25℃, pipe diameter 600mm, inner wall damp with obvious water film, not dried.
[0024] Construction parameters: Centrifugal sprayer speed 500 rpm, moving speed 1 m / min, single spray thickness approximately 2 mm.
[0025] Example 2 The components are the same as in Example 1, except that the mass ratio of A to B is 1:2.5.
[0026] Construction environment: Construction parameters are the same as in Example 1.
[0027] Example 3 The components are the same as in Example 1, except that the mass ratio of A:B is 1:3.0.
[0028] Construction environment: All other construction parameters are the same as in Example 1.
[0029] Comparative Example 1 The components are the same as in Example 1, except that the mass ratio of A:B is adjusted to 1:2.0.
[0030] The construction environment and parameters are the same as in Example 1.
[0031] Comparative Example 2 The components are the same as in Example 1, except that the mass ratio of A:B is adjusted to 1:3.5.
[0032] The construction environment and parameters are the same as in Example 1.
[0033] Comparative Example 3 Formula for Example 1 using existing technology CN120682596A: Component A: 48 parts E-51 epoxy resin, 10 parts ethylene glycol diglycidyl ether, 5 parts benzyl glycidyl ether, 15 parts silica fume, 16 parts fly ash, 4 parts fumed silica, and 2 parts liquid polysulfide rubber.
[0034] Component B: 62 parts of thiourea-modified aliphatic primary amine, 5 parts of n-butanol, 15 parts of corundum, 10 parts of quartz sand, 5 parts of brown corundum powder, and 3 parts of DMP-30.
[0035] The mass ratio of A to B is 10:3, or 1:0.3.
[0036] The construction environment and parameters are the same as in Example 1.
[0037] The performance of the mortars in the above embodiments and comparative examples was tested, and the results are summarized in the table below.
[0038] Performance test results table
[0039] Note: "—" indicates that no valid data could be obtained due to complete failure of the substrate adhesion.
[0040] The above experiments show that the surface drying time of Examples 1-3 is within 20-60 minutes, and the tensile strength reaches 2.7-3.1 MPa after 4 hours, meeting the requirements for rapid water flow. However, the surface drying time of Comparative Example 1 is extended to 90 minutes, and the strength after 4 hours is only 1.5 MPa. Although Comparative Example 2 has a relatively fast surface drying time, the strength development is uneven due to the excessive dryness of the system. Comparative Example 3 cures extremely slowly, failing to surface dry after 2 hours. Analysis indicates that only when the A:B ratio is within the range of 1:2.5-3.0 is the total amount of curing agent in component B sufficient to react quickly and fully with the epoxy resin, achieving a balance between rapid curing and early strength.
[0041] In Examples 1-3, the thickness difference between the top and bottom of the lining was controlled within 0.4 mm, demonstrating excellent uniformity. Comparative Example 1, due to insufficient component B and low system viscosity, showed significant bottom accumulation; Comparative Example 2, due to excessive component B and poor atomization, also resulted in localized thickness unevenness. Comparative Example 3 failed to form effectively at all. This indicates that a rich aggregate ratio of 1:2.5–3.0 is a necessary condition for achieving uniform centrifugal spraying.
[0042] The examples showed good pull-out strength at 4 hours and positive tensile bond strength at 28 days under wet substrate conditions. While Comparative Examples 1 and 2 were higher than Comparative Example 3, they were still significantly lower than the examples, indicating that deviating from the formulation range of this invention significantly weakens wet adhesion. Comparative Example 3 completely lost its adhesive strength due to the emulsification of the curing agent upon contact with water, demonstrating the fundamental defects of existing technologies in wet repair scenarios. The wastewater corrosion resistance retention rate of the examples all exceeded 91%, while that of Comparative Examples 1 and 2 decreased to 78% and 82%, respectively. This was due to the decrease in the uniformity and density of the filler distribution in the continuous phase caused by the formulation deviation. The synergistic effect of the dense aggregate skeleton formed under a high B component ratio and the anti-corrosion filler treated with coupling agent is the key guarantee for long-term durability.
[0043] Comparative Example 3, using the resin-rich formulation specified in CN120682596A, exhibited failure or extremely poor performance across all key performance indicators, particularly failing to function properly on damp surfaces and being completely unsuitable for pipe repair while wet. This invention, by reversing the A:B ratio to 1:2.5–3.0, comprehensively overcomes the shortcomings of existing technologies and delivers unexpected technical benefits.
Claims
1. A two-component, fast-setting epoxy lining repair mortar for trenchless repair of old stormwater and sewage pipes, comprising component A and component B, characterized in that... Component A and Component B are prepared in advance, and the mass ratio of Component A to Component B during construction is 1:2.5 to 3.
0. By weight, The A component consists of the following components: 60-70 parts of bisphenol A epoxy resin, 10-15 parts of reactive diluent, 1-3 parts of defoamer, and 1-2 parts of wetting and penetrating agent. The B component consists of the following components: 50-65 parts of fine quartz sand, 15-25 parts of silica powder, 25-40 parts of polyamide curing agent, 10-15 parts of corrosion-resistant heavy calcium carbonate powder with surface treated with silane coupling agent, and 1-3 parts of coagulation accelerator.
2. The two-component fast-setting epoxy lining repair mortar according to claim 1, characterized in that, The mass ratio of component A to component B is 1:2.
8.
3. The two-component fast-setting epoxy lining repair mortar according to claim 1, characterized in that, By weight, component A contains 65 parts bisphenol A epoxy resin, 12 parts reactive diluent, 2 parts defoamer, and 1.5 parts wetting and penetrating agent; component B contains 55 parts quartz fine sand, 20 parts silica powder, 35 parts polyamide curing agent, 12 parts corrosion-resistant heavy calcium carbonate powder treated with silane coupling agent, and 2 parts coagulation regulator.
4. The two-component fast-setting epoxy lining repair mortar according to claim 1, characterized in that, The reactive diluent is selected from butyl glycidyl ether, C 12 ~C 14 One or more of alkyl glycidyl ethers; the defoamer is an organosilicone defoamer; the wetting and penetrating agent is a polyether-modified polysiloxane.
5. The two-component fast-setting epoxy lining repair mortar according to claim 1, characterized in that, The polyamide curing agent is an adduct of dimer acid-triethylenetetramine condensate and bisphenol A epoxy resin, or a dimer acid type polyamide, wherein the dimer acid type polyamide is formed by the condensation of dimer acid and polyamine, and the polyamine is selected from at least one of diethylenetriamine, triethylenetetramine, and m-phenylenediamine. The amine value of the polyamide curing agent is 180-220 mgKOH / g. The silane coupling agent used in the corrosion-resistant heavy calcium carbonate powder whose surface is treated with silane coupling agent is KH-550 or KH-560.
6. The two-component fast-setting epoxy lining repair mortar according to claim 1, characterized in that, The coagulation accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, and its dosage is adjusted according to the ambient temperature during construction: when the temperature is below 15℃, the dosage is 2.5 to 3 parts; when the temperature is between 15℃ and 25℃, the dosage is 1.5 to 2.5 parts; and when the temperature is above 25℃, the dosage is 1 to 1.5 parts.
7. A method for trenchless repair of old stormwater and sewage pipes, characterized in that, Using the two-component fast-setting epoxy lining repair mortar as described in any one of claims 1 to 6 includes the following steps: Weigh the pre-prepared components A and B at a mass ratio of 1:2.5 to 3.0, mix them evenly, and then spray the mortar evenly onto the inner wall of the pipe under the action of centrifugal force through a centrifugal spraying device to form an inner lining repair layer. During spraying, the inner wall of the pipe is wet or watery and is not pre-dried.
8. The method according to claim 7, characterized in that, During centrifugal spraying, the centrifugal sprayer rotates at 300–800 rpm, moves at 0.5–2 m / min, and achieves a single spray thickness of 1–3 mm. The designed repair thickness is achieved through multiple sprays.
Citation Information
Patent Citations
High-thixotropy epoxy mortar as well as preparation method and application thereof
CN120682596A